Influence of surrounding vegetation on the diversity of social wasps on coffee culture - Jacques, Gabriel de Castro; de Araújo, Bruna Síntia Silva (Revista Agrogeoambiental, 2020)
Every year, coffee crops are affected by pests and diseases that hamper productivity and grain quality. Chemicals used to tackle these issues not only increase production cost, but may also lead to serious problems in the long term. The use of biological control for the management of pest aims to reduce the use of such products and preserve the environment. For being natural predators of these pest insects, social wasps are an effective alternative for biological control. Attractive traps were installed in two areas of coffee culture: one with predominant orchard vegetation, called Orchard-coffee; and the other with an Atlantic forest fragment as predominant surrounding vegetation, called Forestcoffee. The aim was to compare the diversity and abundance of social wasp species that visited the two areas. Bray-Curtis (dis-)similarity between the two areas was low, 0.45, showing surroundings influence in both areas. In total, 208 individuals of 11 species and 4 different genera were collected, with a total Shannon-Wiener (H’) diversity index of 1.591. Orchard-coffee showed a higher number of social wasps, whereas Forest-coffee showed a higher diversity index. The most abundant species in both areas was Polistes versicolor, which can reduce damage caused by coffee pests and has a great potential use in biological control programs.